Low-copy-number repeat sequences flank the DiGeorge/velo-cardio-facial syndrome loci at 22q11. - Halford, S; Lindsay, E; Nayudu, M; Carey, A; Baldini, A; Scambler, P (1993)
DiGeorge syndrome and velo-cardio-facial syndrome are associated with deletions within 22q11. In attempting to refine the shortest region of overlap for these syndromes we have employed fluorescence in situ hybridisation. The results obtained for some probes indicate the presence of low-copy-number repeat families dispersed through proximal 22q. Several primate species have been examined for the presence or absence of two sequences mapping to pter-22q11. The results suggest a relatively recent evolutionary origin for these sequences and the loss of one sequence during the course of primate evolution.